2023
DOI: 10.1186/s12889-023-15177-x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional eating in relation to psychological stress during COVID-19 pandemic: a cross-sectional study in faculty of medicine, Tanta University, Egypt

Abstract: Background Stress, anxiety, and depression resulting from the COVID-19 pandemic as well as subsequent restrictive measures had a negative impact on eating behaviors. This study aimed to determine the emotional eating behaviors and the perceived stress level and to assess the relation between them among adults in the faculty of medicine during the late period of lockdown during the COVID-19 pandemic. Methods This was a cross-sectional study among 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…It resembles information from surveys conducted during the COVID-19 pandemic in Saudi Arabia, Spain, India, and China. 41 Thus, in this study, the students also might have stress due to pandemic situation and lead them to emotional and external eating behavior.…”
Section: Discussionmentioning
confidence: 85%
“…It resembles information from surveys conducted during the COVID-19 pandemic in Saudi Arabia, Spain, India, and China. 41 Thus, in this study, the students also might have stress due to pandemic situation and lead them to emotional and external eating behavior.…”
Section: Discussionmentioning
confidence: 85%
“…Emotional eating (EE) is defined as the tendency to overeat as a regulation mechanism, i.e., coping with negative emotions, depression, anxiety, and stress [ 27 ]. EE is characterised by an inability to distinguish between the physiological sensation of hunger and the desire to use food as a strategy to cope with negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…While research on this topic remains scarce in Arab countries, some available evidence has shown that globalization and substantial sociocultural changes gave rise to the thin ideal and increased risk for dieting-, and disturbed-eating behaviors [ 8 ]. For instance, previous studies emerging from the Arab world documented high prevalence rates of binge eating (e.g., [ 9 11 ]), retrained eating (e.g., [ 12 , 13 ]), and emotional eating (e.g., [ 14 16 ]). Previous findings also suggested that around 40% of the Arab adolescent and adult population of both genders is on a diet [ 8 ].…”
Section: Introductionmentioning
confidence: 99%